The Spectrum and Eigenvectors of the Laplacian Matrices of the Brualdi-Li Tournament Digraphs - Xiaogen Chen (Journal of Applied Mathematics)
Let m≥1 be an integer, let ℬ2m denote the Brualdi-Li matrix of order 2m, and let ℒℬ2m denote the Laplacian matrices of Brualdi-Li tournament digraphs. We obtain the eigenvalues and eigenvectors of ℒℬ2m.